Farmakogenomika in informacijski izzivi - Ferk, Polonca (Informatica Medica Slovenica, 2008)
Pharmacogenomics is an interdisciplinary field which merges knowledge from pharmacology and genomics. Its basic aim is to find out how the unique genotype of an individual determines specific pharmacological responses. To beable to discover clinically relevant associations between the specific genotype and pharmacological response, huge amounts of data should be collected from different sources and further analyzed which is possible only by using suitable and effective informatics tools. In the paper a clinically relevant pharmacogenomic example is first presented and then contemporary informatics challenges are described.
Keywords: Aleli; Alleles; Breast Neoplasms; Citokrom P-450 CYP2D6; Cytochrome P-450 Cyp2d6; Dojka, novotvorbe; Drug Therapy; Farmakogenetika; farmakogenomika; genetika; Genotip; Genotype; Informacijski sistemi; informatika; Information Systems; Pharmacogenetics; Polimorfizem (genetika); Polymorphism (Genetics); Preživetje, analiza; Survival Analysis; Tamoksifen; Tamoxifen